2018
DOI: 10.3389/fnhum.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Gaze Direction Modulates Neural Processing of Prosocial Decision Making

Abstract: Gaze direction is a common social cue implying potential interpersonal interaction. However, little is known about the neural processing of social decision making influenced by perceived gaze direction. Here, we employed functional magnetic resonance imaging (fMRI) method to investigate 27 females when they were engaging in an economic exchange game task during which photos of direct or averted eye gaze were shown. We found that, when averted but not direct gaze was presented, prosocial vs. selfish choices wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…As the decision to trust is concerned with perspective-taking, it should activate brain regions involved in theory-of-mind tasks (Fehr and Camerer, 2007). Moreover, researchers found the STG was involved in the processing of gaze direction in a modified trust game (Sun et al, 2018). A previous study that focused on the neurobiological correlates of conformity during mental rotation task has reported that the presence of external information was associated with decreased activation in the mental rotation neural network (Berns et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As the decision to trust is concerned with perspective-taking, it should activate brain regions involved in theory-of-mind tasks (Fehr and Camerer, 2007). Moreover, researchers found the STG was involved in the processing of gaze direction in a modified trust game (Sun et al, 2018). A previous study that focused on the neurobiological correlates of conformity during mental rotation task has reported that the presence of external information was associated with decreased activation in the mental rotation neural network (Berns et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction might influence the participants' decisions and the underlying neural processes. For example, in the context where participants could interact with others (Sun, Lee, Wang, & Chan, ; Sun, Shao, Wang, & Lee, ), fewer dishonest choices were made when participants interacted with human than computer investors and distinct neural processing during lying were involved when the decision maker considers the interests of the recipient (Sun et al, ). Therefore, the lack of interaction in our current design should be considered as a limitation and the effect of interaction on deception decision‐making should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“… Social Analysis: Eye gaze helps in understanding the ability of an individual in paying attention to any useful information [151]. Gaze direction along with magnetic resonance imaging technique helps in developing potential interpersonal interaction [152, 153]. Sports: Eye movements helps athletes in anticipating where exactly the ball will bounce [154].…”
Section: Discussion About Research Objectives and Potential Future Amentioning
confidence: 99%